Consumer Protection Regulations in Life Insurance industry and its challenges: An empirical analysis from Indonesia - Nicholas L Tobing, Agustinus; ., . (International Journal of Engineering and Technology, 2018)
Trust is a crucial factor in the financial industry. Some financial scandals that had impacted Indonesia include the economic crisis in 1998 and have encouraged the regulator to apply adequate consumer protection for the people of Indonesia. In addition, the existence of adequate consumer protection will have a direct impact on the Indonesian financial industry, especially the life insurance sector where the penetration rate is still low in the last 10 years. In the Indonesian context, the implementation of consumer protection is immature and inconsistent. Based on empirical research, this paper explored the existing conditions of consumer protection implementation across life insurance industry in Indonesia. Moreover, this paper also analyzed the perception of the benefits and the challenges in implementing such requirements. The study found that consumer protection is still at the work in progress stage, inconsistent and not optimally implemented although there are number of benefits and risks if it were implemented as required. This condition has arisen due to the lack of regulatorâ€™s commitment in the consistent implementation, lack of assurance on the quality, improper selling process, as well as limitations in capability and competence in the appointed dispute resolution body. This study suggests a number of actions: [1] Periodic regulator quality assurance for the quality of implementation in the form of assurance review and sanctions impose; [2] strengthening the need based selling for life insurance companies; [3] developing an effective and measurable financial literacy and financial inclusion programs for consumers; [4] building a life insurance product and process related competency and capability of the arbitrator and mediator from the appointed dispute resolution; and [5] establishing awareness and the existence of the dispute resolution body across cities in Indonesia. Â